Evaluating engineering students performance in physics courses during foundation studies - Hari Z.; Anuar A.; Mokhtar M.Z.; Mokhtar R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education; Engineering; Foundations; Physics; Students; Teaching; Engineering foundation; Engineering program; Teaching and learning; Engineering education